Oxidation States, Stability, and Reactivity of Organoferrate Complexes - Parchomyk, Tobias; Demeshko, Serhiy; Meyer, Franc; Koszinowski, Konrad (Journal of the American Chemical Society, 2018)
We have applied a combination of electrospray-ionization mass spectrometry, electrical conductivity measurements, and Mössbauer spectroscopy to identify and characterize the organoferrate species R n Fe m – formed upon the transmetalation of iron precursors (Fe(acac)3, FeCl3, FeCl2, Fe(OAc)2) with Grignard reagents RMgX (R = Me, Et, Bu, Hex, Oct, Dec, Me3SiCH2, Bn, Ph, Mes, 3,5-(CF3)2-C6H3; X = Cl, Br) in tetrahydrofuran. The observed organoferrates show a large variety in their aggregation (1 ≤ m ≤ 8) and oxidation states (I to IV), which are chiefly determined by the nature of their organyl groups R. In numerous cases, the addition of a bidentate amine or phosphine changes the distributions of organoferrates and affects their stability. Besides undergoing efficient intermolecular exchange processes, several of the probed organoferrates react with organyl (pseudo)halides R′X (R′ = Et, i Pr, Bu, Ph, p-Tol; X = Cl, Br, I, OTf) to afford heteroleptic complexes of the type R3FeR′–. Gas-phase fragmentation of most of these complexes results in reductive eliminations of the coupling products RR′ (or, alternatively, of R2). This finding indicates that iron-catalyzed cross-coupling reactions may proceed via such heteroleptic organoferrates R3FeR′– as intermediates. Gas-phase fragmentation of other organoferrate complexes leads to β-hydrogen eliminations, the loss of arenes, and the expulsion of organyl radicals. The operation of both one- and two-electron processes is consistent with previous observations and contributes to the formidable complexity of organoiron chemistry.